THE INFLUENCE OF CLIMATE ELEMENTS ON THE YIELD OF AGRICULTURAL CROPS IN THE AREA OF SUMADIJA IN SERBIA - Petrović, Gordana; Labović, Bojan; Dašić, Boban (Economics of Agriculture, 2019)
The goal of this paper is to examine the existence of correlation between temperature and precipitation as independent variables and crop yield (wheat, corn) as dependent variable by applying Spearmans rank correlation coefficient. As the research field, region of Gruža is taken, more precisely county of Knić. Climate features of previously mentioned territory are obtained by monitoring the climate elements condition (temperature and precipitation) for the time period from 1991 to 2011 in weather stations Kragujevac, Kraljevo and Rudnik. Shifts in climate elements values are usually consequences of climate changes, which manifest in our country and shave significant impact to crop yield.